Immunomodulatory therapy for the management of severe COVID-19. Beyond the anti-viral therapy: A comprehensive review - Alijotas-Reig, Jaume (Autoimmun Rev, 2020)
Severe Acute Respiratory Syndrome related to Coronavirus-2 (SARS-CoV-2), coronavirus disease-2019 (COVID-19) may cause severe illness in 20% of patients. This may be in part due to an uncontrolled immune-response to SARS-CoV-2 infection triggering a systemic hyperinflammatory response, the so-called “cytokine storm”. The reduction of this inflammatory immune-response could be considered as a potential therapeutic target against severe COVID-19. The relationship between inflammation and clot activation must also be considered. Furthermore, we must keep in mind that currently, no specific antiviral treatment is available for SARS-CoV-2. While moderate-severe forms need in-hospital surveillance plus antivirals and/or hydroxychloroquine; in severe and life-threating subsets a high intensity anti-inflammatory and immunomodulatory therapy could be a therapeutic option. However, right data on the effectiveness of different immunomodulating drugs are scarce. Herein, we discuss the pathogenesis and the possible role played by drugs such as: antimalarials, anti-IL6, anti-IL-1, calcineurin and JAK inhibitors, corticosteroids, immunoglobulins, heparins, angiotensin-converting enzyme agonists and statins in severe COVID-19.